Business continuity management and supply chain disruptions: A case of humanitarian organizations in Cyclone Idai in Zimbabwe - Judith Moyo; Simba Mutsvangwa; Tichakunda Valentine Chabata; Lidion Sibanda; Felix Chari (Cogent Business & Management, 2023)
Catastrophic events, such as cyclones, floods, droughts, terrorism, or cybercrime, are astronomically on the increase the world over. These events disrupt businesses' smooth continuity leading to reputational digital data and financial losses among others. Zimbabwe's districts of Chimanimani and Chipinge in March 2019 experienced a catastrophic Cyclone Idai that highly disrupted various important business activities and the associated supply chains. This study, therefore, focuses on the impact of business continuity and organizational performance on mitigating the disruptive effects on major supply chains during a disaster. Ordinary Least Squares (OLS) regression model was used to analyse the relationship between supply chain disruption and business continuity. The study had a population of 82 humanitarian organizations and the researchers successfully administered questionnaires to a sample of 65 humanitarian organizations that participated in relief operations during Cyclone Idai in Zimbabwe. The results show that business continuity has a negative and significant effect on supply chain disruption. At 5% level of significance, business continuity has a positive effect of about 8%. This means that a marginal change in business continuity will result in significant 8% influence on mitigation of supply chain disruption in humanitarian relief efforts. The study findings will be useful to practitioners such as supply chain managers in coming up with strategies in case of supply chain disruption threats due to unseen shocks.
Keywords: 650; business continuity; Cyclone Idai; disasters; supply chain disruptions